2021
DOI: 10.1101/2021.01.03.21249162
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 induces a durable and antigen specific humoral immunity after asymptomatic to mild COVID-19 infection

Abstract: Current SARS-CoV-2 serological assays generate discrepant results, and the longitudinal characteristics of antibodies targeting various antigens after asymptomatic to mild COVID-19 are yet to be established. This longitudinal cohort study including 1972 healthcare workers, of which 386 participants exhibited antibodies against the SARS-CoV-2 spike antigen at study inclusion, reveal that these antibodies remain detectable in the vast majority of participants, 98%, at least four months post infection, despite ha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
3
11
0
2
Order By: Relevance
“…Our findings partially confirm the results of Havervall and colleagues who followed-up 2300 previously SARS-CoV-2 infected healthcare workers in Sweden and found the average time for the reduction of anti-SARS-CoV IgG below the positive cut-off point between 4-6 months [22]. They also found the association between higher immune response levels and more severe symptoms statistically significant similar to the study by Long et al conducted earlier on 37 asymptomatic persons from China [4, 22]. The lack of statistical significance between symptom severity and level of immune response in our study is potentially linked to our limited sample size.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings partially confirm the results of Havervall and colleagues who followed-up 2300 previously SARS-CoV-2 infected healthcare workers in Sweden and found the average time for the reduction of anti-SARS-CoV IgG below the positive cut-off point between 4-6 months [22]. They also found the association between higher immune response levels and more severe symptoms statistically significant similar to the study by Long et al conducted earlier on 37 asymptomatic persons from China [4, 22]. The lack of statistical significance between symptom severity and level of immune response in our study is potentially linked to our limited sample size.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have observed relatively stable levels of IgG to the spike (S) protein after three 11,6 , four 12,13 and six to eight months 2,9,14-16 . However, others reported that IgG only lasted around 3-4 months PSO 17,18 . Many studies consistently observe that IgG to the nucleocapsid (N) protein, found inside the virus or infected cells, decay faster than IgG to S, being a marker of a most recent infection but less sensitive for assessing population seroprevalence 2,13-20 .…”
Section: Introductionmentioning
confidence: 99%
“…Data from 26 studies (8, 9, 11, 12, 16, 17, 29, 47, 49-53, 56, 57, 60, 63, 64, 67, 69, 71, 75, 78, 81, 82, 84), with 3092 participants were available for evaluation of the prevalence of detectable IgG after recovery. The pooled prevalence of detectable IgG after recovery was 89.0% (95%CI 72.8 – 99.0, I 2 =89.7%, p<0.01, 8 studies) within 1 month, 92.6% (95%CI 86.9 – 96.9, I 2 =57.7%, p<0.01, 4 studies) at >1 - <3 months, 91.4% (95%CI 84.5-96.3, I 2 =84.3%, p<0.01, 9 studies) at 3-<6 months and 90.4% (95%CI 72.2-99.9, I 2 =89.0%, p<0.01, 5 studies) beyond 6 months (Fig 3 and Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that individuals infected with SARS-CoV-2 develop neutralizing antibodies (7,8), and that, up to 8 months later, most individuals who recover from COVID-19 have evidence of immunological memory (9)(10)(11)(12)(13). However, many of these studies involve small numbers of participants and suffer from loss to follow up.…”
Section: Added Value Of This Studymentioning
confidence: 99%